2003
DOI: 10.1097/01.mp.0000086072.56290.fb
|View full text |Cite
|
Sign up to set email alerts
|

Multicomponent Analysis of the Pancreatic Adenocarcinoma Progression Model Using a Pancreatic Intraepithelial Neoplasia Tissue Microarray

Abstract: A multistep model for pancreatic adenocarcinoma has been proposed recently. In this model, well-defined, noninvasive ductal lesions are recognized as precursors of invasive cancer and have been classified under the nomenclature of pancreatic intraepithelial neoplasia, or PanIN. Increasing evidence suggests that PanINs represent true neoplasms of the pancreatic ductal epithelium, accumulating histologic and genetic abnormalities in their progression toward invasive cancer. We have constructed a tissue microarra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
309
3
7

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 363 publications
(331 citation statements)
references
References 60 publications
12
309
3
7
Order By: Relevance
“…Immunohistochemical studies then confirmed fascin overexpression, not only in infiltrating ductal adenocarcinomas 28,30,31 but also in PanINs. 29,30 The fact that PanINs show fascin upregulation correlated with histological grade increased our interest in fascin expression in IPMNs, because PanINs and IPMNs share the following fundamental characteristics: 5,6 inherently intraductal; composed predominantly of columnar, mucin-producing cells that may grow in a flat configuration or may produce papillae; exhibit a range of cytologic and architectural atypia (mild, moderate and severe); recognized as precursors to Fascin expression in IPMNs of the pancreas H Yamaguchi et al invasive adenocarcinoma; and sequentially accumulate similar genetic alterations with increasing cytoarchitectural atypia. [43][44][45] We showed that fascin overexpression in IPMNs was correlated with increased histological grade by immunohistochemical analysis, followed by a supporting molecular experiment that showed upregulation of fascin mRNA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Immunohistochemical studies then confirmed fascin overexpression, not only in infiltrating ductal adenocarcinomas 28,30,31 but also in PanINs. 29,30 The fact that PanINs show fascin upregulation correlated with histological grade increased our interest in fascin expression in IPMNs, because PanINs and IPMNs share the following fundamental characteristics: 5,6 inherently intraductal; composed predominantly of columnar, mucin-producing cells that may grow in a flat configuration or may produce papillae; exhibit a range of cytologic and architectural atypia (mild, moderate and severe); recognized as precursors to Fascin expression in IPMNs of the pancreas H Yamaguchi et al invasive adenocarcinoma; and sequentially accumulate similar genetic alterations with increasing cytoarchitectural atypia. [43][44][45] We showed that fascin overexpression in IPMNs was correlated with increased histological grade by immunohistochemical analysis, followed by a supporting molecular experiment that showed upregulation of fascin mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…It is required for the formation of actin-based cell-surface protrusions that are essential for cellular migration and cellmatrix adhesion. [15][16][17] In normal epithelial cells, fascin expression is usually absent or very low, but it is significantly upregulated in transformed epithelial cells and several types of human carcinoma such as lung, 18,19 breast, [20][21][22][23] esophagus, 24,25 stomach, 26 colon, 27 pancreas, [28][29][30][31] biliary tract and ampulla, 31,32 ovary, 33 urinary bladder, 34 and skin. 35 Among the above neoplasms, fascin upregulation is most frequently observed in pancreatic infiltrating adenocarcinoma.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…3 Telomere shortening and activating point mutations in the KRAS2 oncogene occur early in PanIN-1 lesions, the p16INK4A/CDKN2A (henceforth referred to as p16) gene is inactivated in intermediate and late lesions (PanINs 2 and 3), and the TP53, MADH4, and BRCA2 genes are inactivated late, in PanIN-3 lesions. [4][5][6][7][8][9][10] …”
mentioning
confidence: 99%
“…3 Telomere shortening and activating point mutations in the KRAS2 oncogene occur early in PanIN-1 lesions, the p16INK4A/CDKN2A (henceforth referred to as p16) gene is inactivated in intermediate and late lesions (PanINs 2 and 3), and the TP53, MADH4, and BRCA2 genes are inactivated late, in PanIN-3 lesions. [4][5][6][7][8][9][10] One of the most important of the genetic alterations in infiltrating adenocarcinoma of the pancreas and in PanIN, as judged by its high prevalence, is inactivation of the p16 gene. The p16 gene is inactivated in 40% of pancreatic cancers by homozygous deletion, in 40% by an intragenic mutation coupled with loss of the second allele, and in 15% by hypermethylation of the p16 gene promoter.…”
mentioning
confidence: 99%